Why Conferences Matter—An Illustration from the International Marine Conservation Congress - Oester, Samantha; Cigliano, John A.; Hind-Ozan, Edward J.; Parsons, E. Christien Michael (Frontiers in Marine Science, 2017)
A major activity in the life of an academic is the professional conference. It is common knowledge that this is a place to present your research, but what about other benefits of attending a conference? Online surveys were distributed to delegates of the 3rd and 4th International Marine Conservation Congresses (IMCCs), with respondents’ (n=100) feedback including that the congresses provided useful new information that will aid: (1) their research (58%); (2) in-the-field conservation (29%); (3) conservation communication (46%); and (4) conservation and management policy making (45%). They also reported gaining new techniques (56%), skills (64%), and novel ideas (70%) to further their research/careers. Nearly all (91%) gained new contacts that improved their research, in-the-field conservation, science communication, and/or conservation policy making. Two-thirds (64%) gained ideas, contacts, and/or lessons could lead to publications. Over a third (39%) gained new ideas, contacts and/or lessons that led to grant proposals, and 36% gained contacts that led to funding. A conference is not just an avenue for a scientist to present their research to the wider community, but it can be an important venue for brainstorming, networking and making vital connections that can lead to new initiatives, papers and funding, in a way that virtual, online meetings cannot. This is why conferences matter.